MINAT WISATAWAN TERHADAP KEPUTUSAN PEMBELIAN BATIK SOLO - SETIAWAN, LATIF (2011)
The purpose of this research is: 1) To analyze factors that influence tourist interest in buying Batik Solo. 2) To determine the dominant factor that influence tourist interest in buying Batik Solo. In this study, using independent and dependent variables. Independent variables are variables that influence the dependent variable, namely: attitude (X1), lifestyle (X2), trend (X3), product (X4), price (X5), brand (X6) and motifs or patterns (X7) , while the dependent variable is the variable that is influenced by independent variables, namely interest of tourists to Buy Batik Solo. To determine the influence of variables influence attitudes, lifestyle, trends, product, price, brand and the motives, this study uses logit model analysis tool and tested with the Wald-Wolfowitz Run Test. Based on the results of Wald-Wolfowitz Run Test showed that attitudes significantly influence tourist interest in buying batik solo, lifestyle variables significant impact on tourist interest in buying batik solo, the variable has a significant trend towards tourist interest in buying batik solo, product variables significantly influence tourist interest in buying batik solo, variables significantly influence the price of tourist interest in buying batik solo, brand variables significant effect on tourist interest in buying batik solo, motive or pattern variables significant impact on tourist interest in buying batik solo, in this case factor The most significant is the price.